PEMANFAATAN MEDIA FLIPBOOK DIGITAL DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS III DI SDS MUHAMADIYAH 2 GARUT - Sintia Rahayu; Dea Asri Pujianti; Rohani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low level of students’ learning interest, which is influenced by the use of less varied and less engaging learning media. In the learning process, media plays an important role in creating an interactive and enjoyable learning environment. One of the media that can be utilized is a digital flipbook, which integrates various multimedia elements such as text, images, audio, and animation to enhance student engagement in learning. This study aims to analyze the utilization of digital flipbook media in improving the learning interest of third-grade students at SDS Muhammadiyah 2 Garut, as well as to examine its advantages and disadvantages in the learning process. The research method used is qualitative with a literature study (library research) approach. Data were collected from various relevant sources such as books, scientific journals, and research articles, and were analyzed using content analysis techniques. The results show that digital flipbook media has several advantages in increasing students’ learning interest through more engaging, interactive, and varied material presentation. This media can improve students’ attention, participation, and understanding of the learning material. However, there are also some limitations, such as inadequate technological facilities and teachers’ limited ability to develop and operate the media. The implication of this study indicates that digital flipbook media can be an effective alternative learning tool to improve students’ learning interest, provided that adequate infrastructure and teachers’ technological competencies are well supported.